The use of portable particle measurement devices to characterise airborne particles generated in various settings. (24th October 2008) - Handy, Rodney; Rodriguez, Monica; Whitt, Michael; Boregowda, Satish; Dues, Joseph; Jackson, Mark
The accurate measurement of ultrafine and submicron sized airborne particles is a challenging task. Since several studies have linked exposures to airborne ultrafine particles to elevated human health risks, the need to assess the concentrations of particles in the workplace that are below one micron in diameter is imperative. Several techniques for directly monitoring micro and nanoparticles are available and others are being tested for their merit. Condensation Nuclei Counters (CNCs), portable condensation particle counters, differential mobility analysers, electron microscopy and other novel approaches to measuring micro and nanoparticles have been employed in investigations. The purpose of this paper is to elucidate the results from three studies involving the measurement of airborne particles with a laser particle counter and condensation nuclei counter. The three environments include: a gambling casino, a Shielded Metal Arc Welding (SMAW) operation and a general manufacturing facility with welding, cutting and grinding operations being performed.